Compatability and equilibrium approach to slender concrete column design (dual project) - Toh, Yi Hui (2017)
This report evaluates and compares the proposed design method with the Australian code AS3600-2001 for slender concrete column. The failure loads of pin-end columns under short term loading and uniaxial bending are used as a pre-determined factor to analyse the data.